Oracle Service Bus 11g development cookbook : over 80 practical recipes to develop service and message-oriented solutions on the Oracle Service Bus /: over 80 practical recipes to develop service and message-oriented solutions on the Oracle Service Bus. (2012) - Unknown
No abstract available